SWOT Analysis Of Marketing Strategy On Elzatta - Firma Donna; Hamidah Tussifah (University of Darussalam Gontor, 2020)
The Muslim population in the world is increasing every year according to the Pew Research Center's Forum on Religion & Public Life. Indonesia declared a world Muslim fashion center in 2020. Elzatta is a hijab brand with the tagline